Breast cancers originating from the major lactiferous ducts and the process of neoductgenesis: Ductal Adenocarcinoma of the Breast, DAB. Issue 153 (August 2022) - Tabár, László; Dean, Peter B.; Lee Tucker, F.; Yen, Amy Ming-Fang; Chang, Rene Wei-Jung; Hsu, Chen-Yang; Smith, Robert A.; Duffy, Stephen W.; Chen, Tony Hsiu-Hsi
Highlights: The major lactiferous ducts are the site of origin of approximately 20% of all breast cancer cases. This poorly understood disease subtype is misdiagnosed as ductal carcinoma in situ (DCIS). Misdiagnosis of a duct forming invasive carcinoma can result in a cascade of improper management decisions. Recognition of neoductgenesis as an invasive breast cancer is a prerequisite for reducing breast cancer death. Neoductgenesis, the hallmark of DAB, has characteristic imaging and histopathologic features. Abstract: Purpose: To call attention to a highly fatal breast cancer subtype arising from the major lactiferous ducts that is currently underdiagnosed as ductal carcinoma in situ (DCIS) with or without microinvasion. Method: All breast cancers diagnosed at the Department of Mammography, Falun Central Hospital, Sweden, since 1977 have been classified according to their mammographic tumour features (imaging biomarkers) and followed up at regular intervals for the past four decades. The imaging biomarkers characteristic of breast cancers apparently arising from the major lactiferous ducts have been correlated with large format thin and thick section histopathology and long-term patient outcome. Results: Breast cancers arising within the major lactiferous ducts propagate intraductally and produce continuously branching neoducts through epithelial-mesenchymal transformation (EMT), an invasive process termed neoductgenesis, which eventually forms a massive tumour burden. The high fatality of this breast cancer subtype indicates its truly invasive nature, although it is conventionally termed ductal carcinoma in situ, DCIS, terminology which is at odds with its poor long-term patient outcome. The neoducts are filled with multiple layers of malignant cells, have no attached lobules, and propagate by forming multiple invasive side branches. These newly formed duct-like structures are surrounded by a desmoplastic reaction (cancer associated fibroblasts, CAFs) and periductal lymphocytic infiltration. The neoducts are tightly packed together in irregular formations bearing no resemblance to the paniculate branching structure of normal lactiferous ducts. Cancers originating from the major ducts have six imaging biomarkers which can be easily recognized at breast imaging. These are described in detail in an accompanying article. Conclusions: Neoductgenesis in the breast, DAB, is similar in appearance and prognosis to ductal adenocarcinoma of the prostate, DAP. We propose the term ductal adenocarcinoma of the breast, DAB, to facilitate its recognition as a distinct invasive breast cancer subtype. The high fatality rates associated with neoductgenesis reflect the failure of current histopathologic diagnostic criteria to effectively guide therapeutic practice. When the neoducts are associated with small stellate/spiculated or spherical/oval-shaped invasive cancers arising from the terminal ductal lobular units (TDLUs), the prognosis and management are erroneously estimated according to the smaller invasive tumour(s), giving a false sense of security often resulting in undertreatment. Recognition that neoductgenesis is an invasive malignancy is a prerequisite for preventing treatment failure.